Digital Handbook Development Design "Religious Board Games" for Early Childhood - Aulia Izzul Haqe; Putri Ayu Wulandari; Windi Wulandari Iman Utama (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to develop teaching materials using a game system that is considered suitable for Early Childhood, which is still in process which is also adjusted to the psychological aspects of students. Teachers also involve students in the learning process through the Digital Guidebook "Religious Board" to stimulate children's brains to develop properly according to their age. This research also uses Thiagarajan's 4-D (Four-D) development model consisting of 5 units, but this research only reaches the design stage. The results of teaching material research according to experts show that the teaching materials developed have very feasible criteria as evidenced by the games played by students in schools, especially kindergartens, get very good appreciation.